Global reflections on COVID-19 and urban inequalities. - Doucet, Brian, 1980-; Melik, Rianne van; Filion, Pierre, 1952- (Bristol University Press, 2021)
COVID-19 is an invisible threat that has hugely impacted cities and their inhabitants. Yet its impact is very visible, perhaps most so in urban public spaces and spaces of mobility. This volume explores the transformations of public space and public transport in response to COVID-19 across the world, both those resulting from official governmental regulations and from everyday practices of urban citizens. The contributors discuss how the virus made urban inequalities sharper and clearer, and redefined public spaces in the 'new normal'.